Molards and Their Relation to Landslides Involving Permafrost Failure - Milana, Juan Pablo (2015)
Molards are conical shaped, often-symmetrical, debris mounds with a distinctive radial grain-size gradation, which were first-named in the Alps over 100 years ago. Historically these features did not receive much academic attention as they were rarely observed. Today, six different interpretations can be applied to molards, and the most recent has suggested a link to permafrost failure. The aim of this research was to test the hypothesis that molards result from the failure of permafrost-bearing ground and subsequent melting of the frozen debris boulders. This hypothesis is tested here by: 1) reviewing the known global distribution of molard-bearing mass movements with respect to permafrost distribution; 2) investigating a landslide in the Andes of Argentina with unequivocal relation to permafrost failure, 3) the survey and interpretation of the external and internal structure of molards, applying sedimentary transport concepts and 4) reproducing molards by laboratory simulation. Results show that, with few exceptions, molards are produced from the melt-out from the ice of permafrost blocks. In particular, a permafrost source of the mass flow is more certain for molard densely populated landslide deposits. This study serves to reappraise the presence of molards as they could be used to track permafrost degradation on mountainous areas and hence climate changes (temperature or precipitation).